Sustainability Aspects of Managerial Process of Creating Material Basis for Tourism - Vujović, Slavoljub M.; Premović, Jelena Đ.; Spajić, Jovan R. (Collection of Papers of the Faculty of Philosophy in Priština, 2018)
Research of and respect for environmental, economic, and socio-cultural principles in the process of creating the material basis are one of the key preconditions for the sustainable development of tourism. The aggravating circumstances when ensuring sustainability—such as creating new and improving the existing material basis (renovation, reconstruction and modernization)—are the expectations of those who create the market demand as a driving factor of the overall development of tourism. The sustainable approach to creating the material basis for tourism requires serious study, planning, and management of the above-mentioned principles in order to secure extensive long-term investments. Numerous environmental groups insist on finding ways to keep the environment healthy and clean without stopping the economic growth, which is one of the global issues in creating the material basis for tourism. In addition to the shareholding and loan capital, one of the ways of financing infrastructure systems is a public-private partnership that involves sharing both benefits and responsibilities and risks in the process of building the material basis, in accordance with the requirements of ecology, economics, and sociology.